Access to Care, Reporting Behaviors, and Quality of Athletic Training Service Interactions for Reserve Officers' Training Corps cadets - Mary Catherine Avey; Amy Hand; Nancy Uriegas; Allison Smith; Zachary Winkelmann (Bowling Green State University, 2021)
Purpose: Reserve Officers' Training Corps (ROTC) programs prepare student-civilians to become leaders through strenuous physical and leadership training. Unlike their student-athlete counterparts who have direct access to athletic training services, ROTC cadets may or may not have a healthcare provider available. The purpose of this study was to examine the access to care and reporting behaviors of ROTC cadets with a secondary aim exploring the quality of healthcare service interactions relative to patient-centered care. Methods: An online survey assessed access to care using a self-report tool on the type of medical providers available to the ROTC cadets (n=132, age=20±3 y) dispersed between the Army, Navy, Air Force, and Marines, and their illness/injury history and reporting behaviors. The participants who sought care for an injury/illness also completed the Consultation and Relational Empathy tool to measure the level of patient-centered care by the healthcare provider with follow-up analysis using the Consultation Care Measure tool for all athletic training service interactions. Data were analyzed using descriptive statistics. Results: ROTC cadets reported access to 2±1 healthcare providers including a designated civilian physician (26.5%), athletic trainer (23.5%), and ROTC peer first responder (14.4%). However, 50.8% of respondents stated they were unsure what healthcare providers were available. In total, 22.7% of cadets reported being injured and 26.5% reported being sick/ill while participating in ROTC activities. Of those who stated they had sustained an injury during ROTC, 59.9% seldomly or never reported their injury. The ROTC cadets who sought healthcare expressed they were satisfied with their injury (35.96±10.60) and illness (35.48±13.10) treatment from a patient-centered viewpoint. Conclusions: The ROTC cadets reported a general unfamiliarity with the healthcare providers available to them. Despite the reporting behaviors, the cadets reported being satisfied with the care they received.